Heat-resistant material, heat-shielding coating system and method for manufacturing heat-resistant material

A heat-resistant material using rare earth titanate with mixed rare earth and Ti ions addresses radiant heating issues in conventional systems, providing effective radiant heat blocking and structural stability for gas turbines and jet engines.

JP2025015428APending Publication Date: 2025-01-30JAPAN FINE CERAMICS CENTER

Patent Information

Application Number
JP2024087520
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-18
Filing Date
2024-05-29
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Conventional heat-shield coating systems for gas turbines and jet engines are inadequate in addressing radiant heating from high-temperature heat sources, as they primarily focus on convective heat management and lack effective radiant heat resistance, leading to potential overheating of substrates.

Method used

A heat-resistant material composed of rare earth titanate (R2Tio5) with a mixture of at least three types of rare earth elements and Ti ions, which selectively absorbs and reflects infrared radiation, providing high structural stability and low thermal conductivity.

Benefits of technology

The material effectively blocks radiant heat, maintains structural integrity under thermal cycling, and reduces thermal conductivity, ensuring the substrate remains cool while maintaining durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015428000001_ABST
    Figure 2025015428000001_ABST
Patent Text Reader

Abstract

To provide heat-resistant materials that have excellent low thermal conductivity, high structural stability, and selective impermeability to infrared rays, a heat-shielding coating system and a method for manufacturing heat-resistant materials.SOLUTION: A heat-resistant material mainly composed of a rare-earth titanate represented by the general formula R2TiO5 (R is at least three types of rare-earth elements) utilizes excitation energy of at least one type of the rare-earth elements to absorb energy of light of specific wavelengths among the light contained in an infrared wavelength region.SELECTED DRAWING: Figure 8
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to heat-resistant materials used, for example, in heat shielding of gas turbines and jet engines, thermal barrier coating systems including the heat-resistant materials, and methods for manufacturing the heat-resistant materials. [Background technology]

[0002] Thermal barrier coating systems used in gas turbines and jet engines include a substrate and a thermal barrier layer disposed on the surface of the substrate. In general, the thermal barrier layer is made of yttria-stabilized zirconia (YSZ), which has low thermal conductivity. This makes it possible to prevent the heat transferred to the surface of the thermal barrier layer by the convection of combustion gas from being transferred to the substrate via the thermal barrier layer.

[0003] However, YSZ undergoes phase separation at high temperatures exceeding 1200° C., and therefore has poor structural stability at high temperatures. In this regard, Patent Document 1 discloses a thermal barrier coating having a top coat made of a high-entropy oxide. The high-entropy oxide is represented by the general formula: M x O y (M is 5 or more elements). The top coat of the thermal barrier coating in the document is made of a high-entropy oxide. Therefore, it is difficult for phase transition to occur due to temperature changes under heat cycle conditions, and has high structural stability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2020 / 142125 Brochure Summary of the Invention [Problem to be solved by the invention]

[0005] However, in conventional thermal barrier coating systems, the radiation heat transfer from a high-temperature heat source is not taken into consideration. That is, although YSZ has low thermal conductivity, it easily transmits radiant heat. Therefore, the substrate is easily heated by the radiant heat from the high-temperature heat source through the YSZ thermal barrier layer. In addition, Patent Document 1 states that M x O y There is no disclosure or suggestion of high entropy oxides represented by a general formula other than the above. Furthermore, Patent Document 1 does not disclose or suggest the radiative heat transmittance, i.e., infrared transmittance, of high entropy oxides. As described above, in conventional thermal barrier coating systems, convective heat transfer is mainly assumed, and radiative heat transfer is not assumed.

[0006] Therefore, an object of the present disclosure is to provide a heat-resistant material that has excellent low thermal conductivity, high structural stability, and selective impermeability to radiant heat, i.e., infrared rays, a thermal barrier coating system, and a method for manufacturing the heat-resistant material. [Means for solving the problem]

[0007] (1) In order to solve the above problems, the heat-resistant material disclosed herein is characterized in that it contains as its main component a rare earth titanate represented by the general formula R2TiO5 (R is at least three rare earth elements), and absorbs the energy of light of a specific wavelength within the infrared wavelength range by utilizing the excitation energy of at least one of the rare earth elements.

[0008] Here, the term "main component" refers to the component with the highest content among all the components constituting the heat-resistant material. The main component is preferably contained in an amount of 40 mol % or more of all the components, more preferably 80 mol % or more of all the components, and even more preferably 98 mol % or more of all the components.

[0009] At least three (three or more) types of rare earth ions and Ti ions are mixed in the cation sites of rare earth titanates. A solid solution phase in which these multiple rare earth ions and Ti ions are randomly mixed results in a high configurational entropy. This makes it possible to increase the structural stability of the solid solution phase, i.e., the heat-resistant material, compared to a case in which two or less (including zero) types of rare earth ions and Ti ions are mixed in the cation sites.

[0010] In addition, the rare earth ions and Ti ions in the cation sites distort the crystal lattice of the rare earth titanate, which reduces the thermal conductivity due to phonon diffusion caused by the crystal lattice distortion, compared to when the rare earth ions and Ti ions are not in the cation sites.

[0011] In addition, rare earth trivalent ions (Sc 3+ , Y 3+ , La 3+ , Lu 3+ The electron shells of the 4f orbitals (excluding the 4f orbitals) have unpaired electrons in the 4f orbitals of the inner shell. The 4f orbitals are split into a plurality of energy levels. The unpaired electrons are excited by the energy of light of a specific wavelength among light included in the infrared wavelength region. The excited unpaired electrons move from the ground level (energy level of the ground state) to the excited level (energy level of the excited state), and then return from the excited level to the ground level. At this time, the energy of the light is consumed, for example, by light emission. That is, the energy of the light is absorbed by the heat-resistant material. Therefore, the opacity of the light (the property of not transmitting at least a part (all or a part) of the light) can be improved. In addition, at least a part of the light of a wavelength that does not match the excitation condition of the unpaired electrons is not absorbed by the heat-resistant material and is reflected. In this respect, the opacity of the light can also be improved.

[0012] In this way, the heat-resistant material has selective opacity to light in the infrared wavelength region. Conversely, it has selective transparency to light. Therefore, for example, by combining the rare earth elements that make up R, it is possible to selectively absorb only the energy of light of a desired wavelength (single or multiple wavelengths).

[0013] (2) In the above-mentioned (1) configuration, it is preferable that the wavelength of the light is in the range of 0.7 μm to 4 μm. With this configuration, it is possible to selectively improve the opacity of light in the near-infrared wavelength range (0.7 μm to 2.5 μm) and the mid-infrared wavelength range (2.5 μm to 4 μm).

[0014] (2-1) In the above-mentioned configuration (2), it is preferable that the wavelength of the light is in the range of 0.7 μm to 2.5 μm. With this configuration, it is possible to selectively improve the opacity against light in the near-infrared wavelength range.

[0015] (2-2) In the above configuration (2), it is preferable that the wavelength of the light is in the range of 2.5 μm to 4 μm. With this configuration, it is possible to selectively improve the opacity against light in the mid-infrared wavelength range.

[0016] (3) In any of the above configurations, it is preferable that R is at least four of the rare earth elements. According to this configuration, at least four types of rare earth ions and Ti ions are mixed in the cation site of the rare earth titanate. This can further increase the structural stability of the heat-resistant material. In addition, the thermal conductivity of the heat-resistant material can be further reduced. In addition, the number of combinations of rare earth elements constituting R increases, so there is a higher degree of freedom in selecting the light to be absorbed by the heat-resistant material.

[0017] (3-1) In the above configuration (3), it is preferable that R is at least six of the rare earth elements. According to this configuration, at least six of the rare earth ions and Ti ions are mixed in the cation site of the rare earth titanate. This can further increase the structural stability of the heat-resistant material. Also, the thermal conductivity of the heat-resistant material can be further reduced. Also, since the combinations of the rare earth elements constituting R are increased, the freedom of selection of light to be absorbed by the heat-resistant material is increased.

[0018] (4) In any of the above configurations, the crystal system of the rare earth titanate is preferably a cubic system. This configuration can increase the melting point of the heat-resistant material. Also, the thermal conductivity of the heat-resistant material can be further reduced.

[0019] (5) In any of the above configurations, it is preferable that the rare earth titanate contains each of the rare earth elements constituting the R in equimolar amounts. This configuration further increases the configuration entropy, thereby further increasing the structural stability of the heat-resistant material.

[0020] (6) In order to solve the above problems, the thermal barrier coating system of the present disclosure is characterized by comprising a substrate, and a thermal barrier layer disposed on the front side of the substrate and having a heat-resistant material having any of the above configurations. The thermal barrier coating system of the present disclosure comprises a heat-resistant material having any of the above configurations. As a result, the thermal barrier coating system has excellent low thermal conductivity (low thermal conductivity), high structural stability, and selective impermeability to radiant heat, i.e., infrared rays.

[0021] (6-1) In the above-mentioned configuration (6), it is preferable to have a bonding layer interposed between the substrate and the thermal barrier layer. With this configuration, it is possible to reduce thermal stress caused by the difference in thermal expansion between the substrate and the thermal barrier layer.

[0022] (7) In order to solve the above problems, the manufacturing method of a heat-resistant material disclosed herein is a manufacturing method of a heat-resistant material having any of the above configurations, characterized in that it includes an R determination step of determining R so that the rare earth element having excitation energy corresponding to the energy of the light to be absorbed is included in the light included in the infrared wavelength region.

[0023] According to this configuration, it is possible to design a heat-resistant material that has excellent low thermal conductivity, high structural stability, and selective impermeability to radiant heat, i.e., infrared rays. Also, the heat-resistant material can be manufactured based on this design. Effect of the Invention

[0024] According to the present disclosure, it is possible to provide a heat-resistant material having excellent low thermal conductivity, high structural stability, and selective opacity to infrared rays, a thermal barrier coating system, and a method for manufacturing a heat-resistant material. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a cross-sectional view in the front-rear direction of a thermal barrier coating system according to a first embodiment. [Diagram 2] FIG. 2 is an energy level diagram for rare earth trivalent ions. [Diagram 3] FIG. 3 is a cross-sectional view in the front-rear direction of the thermal barrier coating system according to the second embodiment. [Figure 4] FIG. 4 is a diagram of the crystal structure of R2TiO5. [Diagram 5] FIG. 5 is the diffraction pattern of Example No. 5. [Figure 6] FIG. 6 is the diffraction pattern of Example No. 10. [Figure 7] FIG. 7 is a graph showing the optical characteristics of Example No. 2. [Figure 8] FIG. 8 is a graph showing the optical characteristics of Example No. 4. [Figure 9] FIG. 9 is a graph showing the optical characteristics of Example No. 5. [Figure 10]FIG. 10 is a graph showing the optical characteristics of Example No. 10. [Figure 11] FIG. 11 is a graph showing the optical characteristics of Comparative Example No. 6. [Figure 12] FIG. 12 is a graph showing the optical characteristics of Comparative Example No. 7. [Figure 13] FIG. 13 is a graph showing the optical characteristics of the comparative example (4YSZ). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, embodiments of the heat-resistant material, the thermal barrier coating system, and the method for producing the heat-resistant material according to the present disclosure will be described.

[0027] First Embodiment (Thermal barrier coating system, heat-resistant materials) First, the configuration of the thermal barrier coating system and heat-resistant material of this embodiment will be described. Fig. 1 shows a cross-sectional view of the thermal barrier coating system of this embodiment in the front-back direction. Fig. 1 also shows a schematic segment structure of a thermal barrier layer 4. As shown in Fig. 1, the thermal barrier coating system 1 includes a thermal barrier layer 4, a bonding layer 3, and a substrate 2 from the front side (upstream side of the heat transfer path) to the back side (downstream side of the heat transfer path).

[0028] The substrate 2 is a member to be protected by the thermal barrier layer 4. The substrate 2 is made of a Ni-based alloy. The bonding layer 3 is laminated on the front side of the substrate 2. The bonding layer 3 is made of a NiCoCrAlY alloy. The bonding layer 3 has adhesion to the substrate 2 and the thermal barrier layer 4. The thermal barrier layer 4 is laminated on the front side of the bonding layer 3. The thermal barrier layer 4 is the outermost layer (top coat) of the thermal barrier coating system 1. As shown diagrammatically in FIG. 1, the thermal barrier layer 4 is dense and has a segment structure consisting of a plurality of segments (columnar structures) 40 extending in the front-rear direction. A gap 41 is defined between any two segments 40 adjacent in the surface direction (direction perpendicular to the front-rear direction).

[0029] The heat shield layer 4 is made of a heat-resistant material. Rare earth titanate, which is the main component of the heat-resistant material, is expressed by the general formula R2TiO5 (R is at least three kinds of rare earth ions). Under heat cycle conditions, the crystal system of the rare earth titanate maintains a cubic system (space group Fm-3m(225)). O ions or vacancies are located at the 8c site. Rare earth ions or Ti ions are located at the 4a site.

[0030] The rare earth elements contained in R of rare earth titanate (general formula R2TiO5) include scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). R is three or more rare earth elements selected from these rare earth elements. The three or more rare earth elements are each contained in an equimolar amount.

[0031] (Thermal barrier coating system, manufacturing method for heat-resistant materials) Next, a method for manufacturing the thermal barrier coating system and the heat-resistant material according to the present embodiment will be described. The method for manufacturing the thermal barrier coating system includes an R determination step, a raw material preparation step, a bonding layer lamination step, and a thermal barrier layer lamination step.

[0032] In the R determination step, three or more rare earth elements constituting R in rare earth titanate (general formula R2TiO5) are determined. That is, the heat shielding layer 4, i.e., the heat-resistant material, is required to have the function of absorbing the energy of light of a desired wavelength among light included in the infrared wavelength range. In this step, three or more rare earth elements constituting R are determined in order to impart this function to the heat-resistant material. Specifically, R is determined so as to include rare earth elements having excitation energy corresponding to the energy of the light to be absorbed.

[0033] In the raw material preparation step, a raw material having a target composition (a composition in which the rare earth elements that make up R determined in the R determination step are blended in equimolar amounts) is prepared. The raw material is prepared, for example, by spray pyrolysis. In this case, a raw material solution having the target composition is prepared, and the mist of the raw material solution is dried and pyrolyzed to produce a powder of rare earth titanate (general formula R2TiO5), i.e., a heat-resistant material, which is then collected.

[0034] In the bonding layer lamination step, a bonding layer 3 is laminated on the surface of the substrate 2 by low-pressure plasma spraying. In the thermal barrier layer lamination step, a thermal barrier layer 4 is laminated on the surface of the bonding layer 3 by, for example, electron beam physical vapor deposition (EB-PVD). That is, first, the substrate 2 on which the bonding layer 3 is laminated and the powdered raw material prepared in the raw material preparation step are placed in a vacuum chamber. Next, the raw material is heated and evaporated by an electron beam. The evaporated raw material is deposited on the surface of the preheated bonding layer 3 to form the thermal barrier layer 4.

[0035] (Action and effect) Next, the effects of the heat-resistant material, the thermal barrier coating system, and the manufacturing method of the heat-resistant material of this embodiment will be described. The thermal barrier layer 4 of the thermal barrier coating system 1 is made of a heat-resistant material. At least three types of rare earth ions and Ti ions are mixed in the cation sites of the rare earth titanate of the heat-resistant material. A solid solution phase in which these rare earth ions and Ti ions are irregularly mixed increases the configurational entropy. For this reason, the solid solution phase is unlikely to undergo a phase transition due to temperature changes under heat cycle conditions. Therefore, the structural stability of the solid solution phase, that is, the heat-resistant material, can be increased.

[0036] The crystal lattice of rare earth titanates is distorted due to the mixture of rare earth ions and Ti ions at the cation sites, which reduces the thermal conductivity due to phonon diffusion caused by the distortion of the crystal lattice.

[0037] Rare earth trivalent ions (Sc 3+ , Y 3+ , La 3+ , Lu3+ The electron shells of rare earth ions (except for ) have an unpaired electron in the inner 4f orbital. Figure 2 shows the energy levels of trivalent rare-earth ions. Note that Figure 2 is a partial modification of "Fig. 8. Observed energy levels of the trivalent rare-earth ions" in "GH Dieke, HM Rosswhite, Applied Optics, 2,675 (1963)" (item names on the left vertical axis and right vertical axis added). The left vertical axis indicates energy, and the right vertical axis indicates the wavelength of light. For example, the near-infrared wavelength region is from 0.7 μm to 2.5 μm, and the mid-infrared wavelength region is from 2.5 μm to 4 μm.

[0038] As shown in Figure 2, the 4f orbital of the inner shell is split into multiple energy levels. The unpaired electron is excited by the energy of light of a specific wavelength included in the infrared wavelength range. The excited unpaired electron moves from the ground level to the excited level, and then returns from the excited level to the ground level. During this process, the energy of the light is consumed by radiative transitions and non-radiative transitions. In other words, the energy of the light is absorbed by the heat-resistant material.

[0039] As an example, the Yb 3+ In the case of , the unpaired electron is excited by the energy of light with a wavelength of 0.98 μm, which is included in the near-infrared wavelength region, and rises to the ground state (symbol 2 F 7 / 2 ) to the excited level (term symbol 2 F 5 / 2 ) and returns from the excited level to the ground level. At this time, the energy of the light is consumed by light emission. In other words, the energy of the light is absorbed by the heat-resistant material.

[0040] In this way, the heat-resistant material can absorb the energy of the desired light. This can improve the light impermeability (the property of not transmitting at least a part (all or a part) of the light). Furthermore, at least a part of the light having a wavelength that does not match the excitation condition of the unpaired electrons is reflected by the heat-resistant material. In this respect, the light impermeability can also be improved.

[0041] In this way, the heat-resistant material has selective opacity to light in the infrared wavelength range. Conversely, it has selective transparency to light. Therefore, the heat-resistant material can selectively absorb only the energy of light of a desired wavelength (single or multiple wavelengths) depending on the combination of rare earth elements that make up R.

[0042] The crystal system of the rare earth titanate heat-resistant material is a cubic system. This allows the melting point of the heat-resistant material to be increased. It also allows the thermal conductivity to be reduced. Rare earth titanate contains equimolar amounts of the multiple rare earth elements that make up R. This allows the configurational entropy to be higher than when the rare earth elements are not contained in equimolar amounts. This allows the structural stability of the heat-resistant material to be increased.

[0043] The thermal barrier layer 4 of the thermal barrier coating system 1 is made of the above-mentioned heat-resistant material. Therefore, the thermal barrier layer 4 has low thermal conductivity. Therefore, it is possible to suppress the transfer of heat from a heat source on the front side of the thermal barrier layer 4 to the bonding layer 3 and the base material 2 on the back side of the thermal barrier layer 4 through the thermal barrier layer 4. In addition, the thermal barrier layer 4 has high structural stability. Therefore, even under heat cycle conditions, the thermal barrier layer 4 is not easily peeled off from the bonding layer 3. In addition, the thermal barrier layer 4 is not easily deteriorated. In addition, the thermal barrier layer 4 has selective impermeability to radiant heat, that is, infrared rays. Therefore, it is possible to suppress the transfer of heat caused by light of a specific wavelength from a heat source on the front side of the thermal barrier layer 4 to the bonding layer 3 and the base material 2 on the back side of the thermal barrier layer 4 through the thermal barrier layer 4. In addition, a gap 41 is defined between any two segments 40 adjacent to each other in the surface direction. Therefore, it is possible to suppress the generation of thermal stress in the thermal barrier coating system 1 when used under heat cycle conditions. In addition, the bonding layer 3 is interposed between the substrate 2 and the thermal barrier layer 4. This makes it possible to reduce thermal stress caused by the difference in thermal expansion between the substrate 2 and the thermal barrier layer 4.

[0044] The thermal barrier coating system and the manufacturing method for heat-resistant material have an R determination process. This makes it possible to design a heat-resistant material that has excellent low thermal conductivity, high structural stability, and selective impermeability to radiant heat, i.e., infrared rays. In addition, the spray pyrolysis method is used in the raw material preparation process. This makes it possible to control the composition of the rare earth titanate powder simply and with high precision by precisely adjusting the composition of the raw material solution of the target composition. In addition, it is possible to obtain spherical particles (powdered heat-resistant material) with a uniform particle size.

[0045] Second Embodiment The heat-resistant material, thermal barrier coating system, and method for producing a heat-resistant material of this embodiment differ from the heat-resistant material, thermal barrier coating system, and method for producing a heat-resistant material of the first embodiment in that the thermal barrier layer does not have a segment structure. Here, only the difference will be described.

[0046] Fig. 3 shows a cross-sectional view of the thermal barrier coating system of this embodiment in the front-rear direction. The same reference numerals are used to denote parts corresponding to those in Fig. 1. As shown in Fig. 3, the thermal barrier layer 4 does not include the segments 40 and gaps 41 shown in Fig. 1.

[0047] The heat-resistant material, thermal barrier coating system, and manufacturing method of the heat-resistant material of this embodiment have the same effects as the heat-resistant material, thermal barrier coating system, and manufacturing method of the heat-resistant material of the first embodiment in the parts having common configurations. According to the thermal barrier coating system 1 of this embodiment, the thermal barrier layer 4 covers the surface of the bonding layer 3 without any gaps. Therefore, the transfer of radiant heat to the substrate 2 can be suppressed.

[0048] <Other> The embodiments of the heat-resistant material, the thermal barrier coating system, and the method for manufacturing the heat-resistant material according to the present disclosure have been described above. However, the embodiments are not particularly limited to the above-described embodiments. Various modifications and improvements that can be made by those skilled in the art are also possible.

[0049] The crystal system of the rare earth titanate heat-resistant material is not particularly limited, and may be a cubic system (space group Fm-3m(225)), a hexagonal system (space group P63 / mmc(194)), an orthorhombic system (space group Pnma(62)), or any two crystal systems selected from these crystal systems.

[0050] The wavelength of light to be absorbed by the heat-resistant material is not particularly limited. The wavelength may be in the infrared wavelength region (0.7 μm to 1 mm). The wavelength may be in at least one of the near-infrared wavelength region (0.7 μm to 2.5 μm) and the mid-infrared wavelength region (2.5 μm to 4 μm).

[0051] 64% of the radiant heat energy of a black body at 1700°C (assuming the temperature of the combustion gas in a gas turbine) is included in the wavelength range (0.5 μm or more and 2.5 μm or less). In light of this, the wavelength of light to be absorbed by the heat-resistant material may be set so as to be included in this wavelength range. The wavelength of light to be absorbed may be single or multiple.

[0052] There is no particular limitation on the type of rare earth element constituting R. The number of types of rare earth elements may be three, four, five, or six or more. R may contain at least one type of rare earth element that can be excited in response to light that is to be absorbed by the heat-resistant material.

[0053] The compounding ratio of the rare earth elements constituting R is not particularly limited. Three or more kinds of rare earth elements may be contained in equimolar amounts. Also, three or more kinds of rare earth elements may be contained in approximately equimolar amounts. Here, "approximately" means that there is a difference of 0.2% or less between the molar amounts of all rare earth elements constituting R. Also, the molar amounts of the three or more kinds of rare earth elements may be different from each other. In addition to rare earth titanate, the heat-resistant material may contain additives and unavoidable impurities as appropriate. It is sufficient that the main component of the heat-resistant material is rare earth titanate. The heat-resistant material may be used as the heat-shielding layer 4 of the thermal barrier coating system 1, or may be used independently of the heat-shielding layer 4. For example, a block-shaped (e.g., block-shaped) heat-resistant material may be used as a fireproofing material, a furnace material, or the like.

[0054] The method for producing the heat-resistant material is not particularly limited. As shown in Fig. 1 and Fig. 3, when the heat-resistant material is used in a thermal barrier coating system 1 and the thermal barrier coating system 1 has a bonding layer 3, the heat-resistant material may be produced at the same time as laminating the thermal barrier layer 4 on the bonding layer 3. Alternatively, a film-like thermal barrier layer 4 may be produced first, and then the thermal barrier layer 4 may be attached to the bonding layer 3. When the thermal barrier coating system 1 does not have a bonding layer 3, the heat-resistant material may be produced at the same time as laminating the thermal barrier layer 4 on the substrate 2. Alternatively, a film-like thermal barrier layer 4 may be produced first, and then the thermal barrier layer 4 may be attached to the substrate 2.

[0055] When the heat-resistant material is produced alone, the heat-resistant material may be produced by a production method including, for example, the above-mentioned R determination step and raw material preparation step. In this case, after the raw material preparation step, a calcination step of calcining the prepared raw material powder, a crushing step of crushing the calcined body, a molding step of molding the crushed body, a firing step of firing the molded body, a processing step of processing the fired body (grinding, polishing, etc.), etc. may be appropriately added.

[0056] Also, in the early stage of the raw material preparation process (before heat treatment), three or more compounds containing rare earth elements constituting R and a compound containing Ti may be mixed to prepare a mixture so as to obtain a target composition. In this case, a urea decomposition method may be used. Examples of the compounds to be mixed include oxides, hydroxides, sulfates, carbonates, nitrates, phosphates, halides, etc. The compounds may be water-soluble or water-insoluble. The treatment method of the heat treatment furnace used in the heat treatment of the raw material preparation process may be either a continuous type or a batch type. The heat source of the heat treatment furnace may be infrared rays, microwaves, etc.

[0057] The application of the thermal barrier coating system 1 is not particularly limited. It can be used for various high-temperature components such as gas turbine components (nozzles, blades, etc.) for power plants, aircraft, and ships, combustion equipment components, jet engine components, and automobile engine components. The material of the substrate 2 shown in FIG. 1 is not particularly limited. For example, it can be a material containing at least one element selected from Ni, Co, Fe, Nb, Ta, Mo, W, Pt, Ir, Cr, and Al. Specific examples include Ni-based alloys, Co-based alloys, and Fe-based alloys. Ni, Co, Mo, W, Ti, Nb, Cr, and the like may be added to the substrate 2 as appropriate.

[0058] The layer structure of the bonding layer 3 is not particularly limited. It may be a single-layer structure or a multi-layer structure. The material of the bonding layer 3 is not particularly limited. Examples of the bonding layer 3 include an MCrAlY alloy (wherein M is at least one element selected from Ni, Co, and Fe), an aluminide intermetallic compound, and the like. Examples of the MCrAlY alloy include an NiCoCrAlY alloy, a CoNiCrAlY alloy, and an FeCrAlY alloy. Examples of the aluminide intermetallic compound include platinum aluminide and nickel aluminide. The bonding layer 3 does not have to be disposed in the thermal barrier coating system 1. That is, the thermal barrier layer 4 may be directly laminated on the surface of the substrate 2.

[0059] The structure of the thermal barrier layer 4 is not particularly limited. The thermal barrier layer 4 may or may not have a segment structure. The thermal barrier layer 4 may be dense or porous. The thermal barrier layer 4 may have a single-layer structure or a multi-layer structure.

[0060] The manufacturing method of the thermal barrier coating system is not particularly limited. In the case where the manufacturing method includes an R determination step, a raw material preparation step, a bonding layer lamination step, and a thermal barrier layer lamination step, the bonding layer lamination step and the raw material preparation step may each be performed before the thermal barrier layer lamination step. The R determination step may be performed before the raw material preparation step. There is no particular limitation on the order of the bonding layer lamination step, the R determination step, and the raw material preparation step.

[0061] The lamination method of the bonding layer 3 in the bonding layer lamination step is not particularly limited. Examples include low-pressure plasma spraying, atmospheric plasma spraying, sputtering, aluminizing, etc. The lamination method of the thermal barrier layer 4 in the thermal barrier layer lamination step is not particularly limited. Examples include electron beam physical vapor deposition, atmospheric plasma spraying, low-pressure plasma spraying, suspension spraying (suspension plasma spraying, suspension high-velocity flame spraying, etc.), high-velocity flame spraying, sputtering, sintering, etc. Note that electron beam physical vapor deposition and suspension spraying are suitable for forming the segment structure shown in FIG. 1. EXAMPLES

[0062] The evaluation tests performed on the heat-resistant material of the present disclosure will be described below.

[0063] <Sample> Table 1 shows sample Nos. 1 to 9 of the heat-resistant material used in the evaluation test. In the items in Table 1, "CN" stands for coordination number, and "ΔS mix " is the configurational entropy of the cation and anion, and "ΔS(P) mix " indicates the configurational entropy of only the cation, and "R" indicates the gas constant. [Table 1]

[0064] The samples shown in Table 1 are each made of a rare earth titanate represented by the general formula R2TiO5. Among these samples, No. 1 to No. 5 and No. 8 to No. 9 are examples of the heat-resistant material of the present disclosure. R in Examples 1 to 5 and No. 8 is represented by the general formula Yb 1-3x A x B x C x A to C are rare earth elements selected from Y, La, Nd, Gd, Dy, and Er. x is 0.25. In Examples No. 1 to No. 5 and No. 8, R contains equimolar amounts of four kinds of rare earth elements.

[0065] In Example No. 9, R is represented by the general formula La1-3x Nd x Gd x Dy x where x is 0.25. R in Example No. 9 contains equimolar amounts of four rare earth elements (La, Nd, Gd, and Dy). Example No. 10 shown in FIG. 4, which is not shown in Table 1, is an example of the heat-resistant material of the present disclosure, like Nos. 1 to 5 and Nos. 8 to 9. R in Example No. 10 is represented by the general formula Yb 1-5x Nd x Sm x Dy x Ho x Er x where x is 1 / 6. R in Example No. 10 contains equimolar amounts of six rare earth elements (Yb, Nd, Sm, Dy, Ho, and Er). Nos. 6 to 7 are comparative examples. R in Comparative Examples Nos. 6 to 7 all consists of a single rare earth element.

[0066] <Sample manufacturing method> (Manufacturing method for samples No. 1 to No. 8) First, we will explain the manufacturing method of Samples No. 1 to No. 8. The manufacturing method of the samples includes an R determination step, a raw material preparation step, a calcination step, a crushing step, a molding step, a firing step, and a processing step.

[0067] (R determination process) In this process, from among the rare earth elements, R (general formula Yb 1-3x A x B x C x ) are determined. Specifically, the absorption wavelength of each rare earth element is estimated from an energy level diagram (see FIG. 2) or the like, and the rare earth elements A to C are determined. For example, in the case of Example No. 1, Y, La, and Nd are selected from the rare earth elements.

[0068] (Raw material preparation process) In this step, first, a raw material solution having a target composition (a composition in which Yb, A, B, and C are mixed in equimolar amounts) is prepared by the following procedure.

[0069] A titanium tetrachloride aqueous solution "TLA" (manufactured by Toho Titanium Co., Ltd., Ti concentration 17 wt%), ytterbium nitrate hydrate (manufactured by Nippon Yttrium Co., Ltd.), nitric acid A hydrate (manufactured by Kanto Chemical Co., Ltd.), nitric acid B hydrate (manufactured by Kanto Chemical Co., Ltd.), and nitric acid C hydrate (manufactured by Kanto Chemical Co., Ltd.) are mixed to obtain a raw material solution.

[0070] In this process, next, a rare earth titanate powder is produced from the prepared raw material solution by spray pyrolysis. The spray pyrolysis device (ON General Electric Co., Ltd., ACPX-UN-H3SIC-F11-2) is equipped with an atomizer, a heat treatment furnace, and a collector from the upstream side to the downstream side. The atomizer is equipped with an ultrasonic vibrator. The heat treatment furnace is a tubular furnace. The furnace body is provided with three heating zones from the upstream side to the downstream side. The temperatures of the three heating zones can be controlled independently. The collector is equipped with a membrane filter (Merck Ltd., Omnipore, JHWP14225, diameter 142 mm, pore size 0.45 μm).

[0071] When producing rare earth titanate powder, the container containing the raw material solution is set in the atomizer. Mist is generated from the raw material solution by ultrasonic vibration of the atomizer. A carrier gas (e.g., air) is supplied to the spray pyrolysis device from the upstream side to the downstream side. The mist of the raw material solution is transported by the carrier gas and passes through a heat treatment furnace. The temperatures of the three heating sections of the heat treatment furnace are set to 200°C, 500°C, and 800°C from the upstream side to the downstream side. By passing through these heating sections, the mist of the raw material solution dries and becomes a powder. The collector collects the powder using a membrane filter.

[0072] (Pre-firing process, crushing process, molding process, firing process, processing process) In the calcination step, the collected powder is heated at 1400°C for 2 hours in an atmosphere containing oxygen gas to produce a granular calcined body. In the crushing step, the granular calcined body is crushed using a crusher (e.g., a jet mill). In the molding step, the crushed body is press molded at a pressure of 25 MPa. In the sintering step, the molded body is hot pressed (1200-1300°C, 50 MPa, 30 minutes, in Ar), and then heated at 1400°C for 2 hours and 1600°C (or 1750°C) for 2 hours in an air atmosphere, and further heated at 1400°C for 5 hours to sinter. In the processing step, the sintered body is processed (grinded, polished) to produce a sample of a specified size. In this manner, samples No. 1 to No. 8 are manufactured.

[0073] (Manufacturing method for sample No. 9) Next, we will explain the manufacturing method of sample No. 9. The manufacturing method of sample No. 9 is the same as the manufacturing method of the above-mentioned samples No. 1 to No. 8. That is, the manufacturing method of sample No. 9 includes an R determination step, a raw material preparation step, a calcination step, a crushing step, a molding step, a firing step, and a processing step.

[0074] (R determination process) In this process, the absorption wavelength of each rare earth element is estimated from the energy level diagram (see Figure 2) and four rare earth elements, La, Nd, Gd, and Dy, are selected from the rare earth elements.

[0075] (Raw material preparation process) In this process, first, a raw material solution of the target composition (a composition in which La, Nd, Gd, and Dy are each mixed in equimolar amounts) is prepared by mixing an aqueous titanium tetrachloride solution "TLA" (manufactured by Toho Titanium Co., Ltd., Ti concentration 17 wt%), lanthanum nitrate hydrate (manufactured by Kanto Chemical Co., Ltd.), neodymium nitrate hydrate (manufactured by Kanto Chemical Co., Ltd.), gadolinium nitrate hydrate (manufactured by Kanto Chemical Co., Ltd.), and dysprosium nitrate hydrate (manufactured by Kanto Chemical Co., Ltd.).

[0076] In this step, the raw material solution prepared in the raw material preparation step is then subjected to a spray pyrolysis method to produce a rare earth titanate powder. The spray pyrolysis method is the same as the method for producing the samples No. 1 to No. 8 described above.

[0077] (Pre-firing process, crushing process, molding process, firing process, processing process) The details of these steps are the same as those in the manufacturing method for Samples No. 1 to No. 8 described above.

[0078] (Manufacturing method for sample No. 10) Next, we will explain the manufacturing method of sample No. 10. The manufacturing method of sample No. 10 is the same as the manufacturing method of the above-mentioned samples No. 1 to No. 9. That is, the manufacturing method of sample No. 10 includes an R determination step, a raw material preparation step, a calcination step, a crushing step, a molding step, a firing step, and a processing step.

[0079] (R determination process) In this process, the absorption wavelength of each rare earth element is estimated from the energy level diagram (see Figure 2) and six rare earth elements, Yb, Nd, Sm, Dy, Ho, and Er, are selected from the rare earth elements.

[0080] (Raw material preparation process) In this process, first, a raw material solution of the target composition (a composition in which Yb, Nd, Sm, Dy, Ho, and Er are each mixed in equimolar amounts) is prepared by mixing an aqueous titanium tetrachloride solution "TLA" (manufactured by Toho Titanium Co., Ltd., Ti concentration 17 wt%), ytterbium nitrate hydrate (manufactured by Japan Yttrium Co., Ltd.), neodymium nitrate hydrate (manufactured by Kanto Chemical Co., Ltd.), samarium nitrate hydrate (manufactured by Sigma-Aldrich Corporation), dysprosium nitrate hydrate (manufactured by Kanto Chemical Co., Ltd.), holmium nitrate hydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and erbium nitrate hydrate (manufactured by Kanto Chemical Co., Ltd.).

[0081] In this step, the raw material solution prepared in the raw material preparation step is then subjected to a spray pyrolysis method to produce a rare earth titanate powder. The spray pyrolysis method is the same as the method for producing the samples No. 1 to No. 9 described above.

[0082] (Pre-firing process, crushing process, molding process, firing process, processing process) The details of these steps are the same as those in the manufacturing method for Samples No. 1 to No. 9 described above.

[0083] <Structural stability> The structural stability was evaluated by configuration entropy and crystal system. As shown in Table 1, Examples No. 1 to No. 5 had a higher ΔS than Comparative Examples No. 6 to No. 7. mix / R and ΔS(P) mix / R is large, that is, the configurational entropy is high. Therefore, Examples No. 1 to No. 5 have higher structural stability than Comparative Examples No. 6 to No. 7.

[0084] Similarly, as shown in Table 1, Examples No. 8 to No. 9 have a smaller ΔS than Comparative Examples No. 6 to No. 7. mix / R and ΔS(P) mix / R is large, that is, the configurational entropy is high. Therefore, Examples No. 8 to No. 9 have higher structural stability than Comparative Examples No. 6 to No. 7.

[0085] Although not shown in Table 1, ΔS of Example No. 10 mix / R is 0.968. In addition, ΔS(P) of Example No. 10 mix / R is 1.831. Example No. 10 has a smaller ΔS than Comparative Examples No. 6 to No. 7. mix / R and ΔS(P) mix / R is large, that is, the configurational entropy is high. Therefore, Example No. 10 has higher structural stability than Comparative Examples No. 6 to No. 7.

[0086] Figure 4 shows the crystal structure of R2TiO5. The horizontal axis is R 3+The average ionic radius (see Table 1) of rare earth ions (four types in Examples No. 1 to No. 5, No. 8 to No. 9, one type in Comparative Examples No. 6 to No. 7, and six types in Example No. 10) constituting R in (CN=6). The vertical axis is temperature (see Table 1). Phase boundaries (solid lines) L1 to L3 for Examples No. 1 to No. 5 and No. 8 to No. 9 indicate the displacement points (transformation points) of the crystal structure when R is composed of four types of rare earth elements (equal molar ratio). The phase boundaries L1 to L3 were obtained by identifying the crystal phases by X-ray diffraction. The phase boundary L1 is a phase boundary between an orthogonal crystal (one phase) and an orthogonal crystal and a hexagonal crystal (two phases). The phase boundary L2 is a phase boundary between an orthogonal crystal and a hexagonal crystal (two phases) and a hexagonal crystal (one phase). The phase boundary L3 is a phase boundary between hexagonal and cubic crystals. As the ionic radius becomes smaller, the crystal system changes from orthogonal to (orthogonal and hexagonal) to hexagonal to cubic. The phase boundaries (dotted lines) L4 to L5 for Comparative Examples No. 6 to No. 7 indicate the transition points of the crystal structure when R is composed of one rare earth element. The phase boundaries L4 to L5 are quoted from "Fig. 1 Stability diagram of Ln2TiO5polymorphs:" in "Shepelev, YF, Petrova, MA "Crystal structures of Ln2TiO5 (Ln = Gd, Dy) polymorphs." Inorg Mater 44, 1354-1361 (2008)." The phase boundary L4 is a phase boundary between orthogonal and hexagonal crystals. The phase boundary L5 is a phase boundary between hexagonal and cubic crystals. As the ionic radius becomes smaller, the crystal system changes from rectangular to hexagonal to cubic.

[0087] The crystal system of each sample in FIG. 4 was identified by X-ray diffraction. Specifically, powders of each sample were prepared, and for Examples No. 1 to No. 5 and No. 8 to No. 9, the crystal system was identified by X-ray diffraction of the powders treated at 1300°C, 1400°C, 1500°C, and 1600°C, respectively. For Comparative Examples No. 6 to No. 7, the crystal system was identified by X-ray diffraction of the powders treated at 1400°C, 1500°C, and 1600°C, respectively. The X-ray diffraction was performed at room temperature after the samples were held at a predetermined temperature (1300°C, 1400°C, 1500°C, and 1600°C) for 50 hours and cooled. As an example of the diffraction patterns of Examples No. 1 to No. 5 and No. 8 to No. 9, which are quaternary R2TiO5 (R2TiO5 where R is composed of four rare earth elements), FIG. 5 shows the diffraction pattern of Example No. 5. The horizontal axis indicates the diffraction angle, and the vertical axis indicates the diffracted X-ray intensity at each temperature. From FIG. 5, it can be seen that the crystal system of Example No. 5 at 1300°C, 1400°C, 1500°C, and 1600°C is all a cubic system. In other words, it can be seen that in the temperature range of 1300°C to 1600°C, No. 5 maintains the cubic system and does not undergo phase transition.

[0088] Fig. 6 shows the diffraction pattern of the sintered body of Example No. 10, which is a hexa-component R2TiO5 (R2TiO5 consisting of six rare earth elements), sintered at 1600°C. The horizontal axis shows the diffraction angle, and the vertical axis shows the diffracted X-ray intensity. Fig. 6 shows that the crystal system of Example No. 10 at 1600°C is a hexagonal system.

[0089] Also, from Figs. 4 and 6, it is estimated that in the temperature range of 1300°C to 1600°C, No. 10 maintains the hexagonal system and does not undergo phase transition. To explain in detail, as shown in Fig. 4, the phase boundaries L1 to L3 of the quaternary R2TiO5 including Examples Nos. 1 to 5 and Nos. 8 to 9 have a larger slope (absolute value) (the phase boundary line is more prominent) than the phase boundaries L4 to L5 of the unicomponent R2TiO5 (R2TiO5 where R is composed of one type of rare earth element) including Comparative Examples Nos. 6 to 7. That is, the more rare earth elements that constitute R, the larger the slope of the phase boundary line. Therefore, it is estimated that the phase boundary line of the 6-component R2TiO5 including Example No. 10 has a larger slope than the phase boundaries L1 to L3 of the quaternary R2TiO5 including Examples Nos. 1 to 5 and Nos. 8 to 9. Therefore, it is estimated that in the temperature range of 1300°C to 1600°C, No. 10 maintains the hexagonal crystal system and does not undergo phase transition.

[0090] As shown in FIG. 4 and Table 1, the results of X-ray diffraction show that in the temperature range of 1300°C to 1600°C, Example No. 1 maintains the orthorhombic and hexagonal crystal systems, Examples No. 3 to No. 4 maintain the hexagonal crystal system, Example No. 5 maintains the cubic crystal system, Example No. 9 maintains the orthorhombic crystal system, and Example No. 10 maintains the hexagonal crystal system. In the temperature range of 1300°C to 1600°C, Examples No. 1, No. 3 to No. 5, and No. 9 to No. 10 do not undergo phase transition. Therefore, the structural stability is high. Moreover, in the temperature range of 1400°C to 1600°C, Examples No. 2 and No. 8 do not undergo phase transition. Therefore, the structural stability is high.

[0091] As shown in FIG. 4 and Table 1, the results of X-ray diffraction show that Comparative Example No. 6 maintains a hexagonal crystal system at 1400°C to 1600°C. Therefore, the structural stability is high in this temperature range. However, as shown in FIG. 4, the phase boundaries L1 to L3 of Examples No. 1 to No. 5 and No. 8 to No. 9 have a larger gradient (absolute value) than the phase boundary lines L4 to L5 (the phase boundary lines are more steep). Therefore, it is estimated that Examples No. 1 to No. 5 and No. 8 to No. 9 are less likely to undergo phase transition over a wide temperature range than Comparative Example No. 6.

[0092] As described above, it is presumed that the phase boundary line of the 6-component R2TiO5 including Example No. 10 has a steeper slope than the phase boundaries L1 to L3 of the 4-component R2TiO5 including Examples No. 1 to No. 5 and No. 8 to No. 9. Therefore, it is presumed that Example No. 10 is less likely to undergo a phase transition over a wider temperature range than Comparative Example No. 6.

[0093] <Mechanical properties> Mechanical properties were evaluated by elastic modulus and fracture toughness. Elastic modulus was measured by ultrasonic pulse method. Fracture toughness was measured by IF method. As shown in Table 1, Examples No. 4 to No. 5 have elastic modulus and fracture toughness equivalent to Comparative Examples No. 6 to No. 7.

[0094] As shown in Table 1, the elastic modulus and fracture toughness of Examples No. 1 to No. 3 and No. 8 to No. 9 have not been measured. The elastic modulus of Example No. 10, which is not listed in Table 1, is 193 GPa, which is equivalent to the elastic modulus of Examples No. 4 to No. 5 and Comparative Examples No. 6 to No. 7. The fracture toughness of Example No. 10 has not been measured. Among them, Example No. 2 is the same hexagonal crystal as Example No. 4 in the temperature range of 1400 ° C to 1600 ° C, so it is estimated to have the same elastic modulus and fracture toughness as Example No. 4. Also, Example No. 3 is the same hexagonal crystal as Example No. 4 in the temperature range of 1300 ° C to 1600 ° C, so it is estimated to have the same elastic modulus and fracture toughness as Example No. 4. Also, Example No. 10 is the same hexagonal crystal as Example No. 4 in the temperature range of 1300 ° C to 1600 ° C, so it is estimated to have the same fracture toughness as Example No. 4.

[0095] <Thermal properties> The thermal properties were evaluated by thermal conductivity. Specifically, the thermal conductivity at 800°C of each of Examples No. 4 to No. 5 and Comparative Examples No. 6 to No. 7 was measured by the laser flash method (based on JIS R 1611). The thermal conductivity at 800°C of Example No. 10, which is not listed in Table 1, was also measured in the same manner.

[0096] As shown in Table 1, Examples No. 4 to No. 5 have the same thermal conductivity as Comparative Examples No. 6 to No. 7. That is, Examples No. 4 to No. 5 have excellent low thermal conductivity, similar to Comparative Examples No. 6 to No. 7. Moreover, the thermal conductivity of Example No. 10 is 1.47 W / m·K (the same value as Example No. 4). Example No. 10 has excellent low thermal conductivity, similar to Comparative Examples No. 6 to No. 7.

[0097] As shown in Table 1, the thermal conductivity of Examples No. 1 to No. 3 has not been measured. Among them, Example No. 2 is a hexagonal crystal like Example No. 4 in the temperature range of 1400°C to 1600°C, and like Example No. 4, four types of rare earth ions and Ti ions are mixed at the cation site. Therefore, it is estimated that Example No. 2 has a crystal lattice distorted to the same extent as Example No. 4, and has a low thermal conductivity to the same extent as Example No. 4.

[0098] Moreover, in the temperature range of 1300°C to 1600°C, Example No. 3 is a hexagonal crystal like Example No. 4, and has four types of rare earth ions and Ti ions mixed at the cation sites like Example No. 4. Therefore, it is presumed that Example No. 3 has a crystal lattice distorted to the same extent as Example No. 4, and has a thermal conductivity as low as Example No. 4.

[0099] In addition, Example No. 10 has the same hexagonal crystal structure as Example No. 4 in the temperature range of 1300°C to 1600°C, and as described above, the crystal lattice is distorted to the same extent as Example No. 4, and it is estimated to have the same low thermal conductivity as Example No. 4.

[0100] <Optical properties> The optical properties were evaluated by reflectance and transmittance. The reflectance and transmittance were measured using an ultraviolet-visible-near infrared spectrophotometer (Lambda950, manufactured by PerkinElmer Japan Co., Ltd.). Specifically, the reflectance (%) and transmittance (%) of the sample were measured using the spectrophotometer. In addition, the absorbance (%) (=100(%)-reflectance (%)-transmittance (%)) was calculated from the measured reflectance and transmittance, utilizing the fact that radiant energy is the sum of reflected energy, absorbed energy, and transmitted energy.

[0101] FIG. 7 shows the optical characteristics of Example No. 2, FIG. 8 shows the optical characteristics of Example No. 4, FIG. 9 shows the optical characteristics of Example No. 5, FIG. 10 shows the optical characteristics of Example No. 10, FIG. 11 shows the optical characteristics of Comparative Example No. 6, FIG. 12 shows the optical characteristics of Comparative Example No. 7, and FIG. 13 shows the optical characteristics of 4YSZ (Comparative Example).

[0102] As shown in Figure 7, No. 2 (R2TiO5, R = Yb 0.25 Y 0.25 La 0.25 Gd 0.25 Of the rare earth elements (trivalent rare earth ions) that make up R in the formula (II), only Yb has an unpaired electron in the 4f orbital of the inner shell. 3+ , Gd 3+ As shown in Figure 2, Yb 3+ The excitation level of Gd is 0.98 μm. 3+ The excitation level of is outside the wavelength region (0.5 μm to 2.5 μm) shown in Fig. 7. Therefore, in the wavelength region (0.5 μm to 2.5 μm) shown in Fig. 7, No. 2 can absorb the energy of light with a wavelength of about 0.98 μm.

[0103] As in Example No. 2, in the wavelength region (0.5 μm to 2.5 μm), Example No. 4 (R2TiO5, R=Yb 0.25 Y 0.25 Gd 0.25 Dy 0.25 ) is Yb 3+ , Dy 3+ In response to this, Example No. 5 (R2TiO5, R=Yb 0.25 Y 0.25 Dy 0.25 Er 0.25 ) is Yb 3+ , Dy 3+ , Er 3+ In accordance with the above, Example No. 10 (R2TiO5, R=Nd 0.167 Sm 0.167 Dy 0.167 Ho 0.167 Er 0.166 Yb 0.166 ) is Nd 3+ , Sm 3+ , Dy 3+ , Ho 3+ , Er 3+ , Yb 3+ Depending on the wavelength, each of the light sources can absorb light energy around a predetermined wavelength.

[0104] In contrast, in Comparative Example No. 6 (R2TiO5, R=Dy) shown in FIG.3+ In accordance with this, Comparative Example No. 7 (R2TiO5, R=Yb) shown in FIG. 3+ Depending on the wavelength, each can absorb the energy of light near a specific wavelength. Note that 4YSZ (ZrO2 with 4 mol% Y2O3 dispersed and dissolved) shown in Figure 13 cannot locally absorb the energy of light of a specific wavelength.

[0105] Each of Examples No. 4 to No. 5 and No. 10 and Comparative Examples No. 6 to No. 7 can absorb the energy of light near a predetermined wavelength. However, Example No. 4 has two types of rare earth trivalent ions with unpaired electrons in the inner 4f orbitals. Example No. 5 has three types of rare earth trivalent ions with unpaired electrons in the inner 4f orbitals. Example No. 10 has six types of rare earth trivalent ions with unpaired electrons in the inner 4f orbitals. In contrast, each of Comparative Examples No. 6 to No. 7 has only one type of rare earth trivalent ion with unpaired electrons in the inner 4f orbitals. Therefore, compared to Comparative Examples No. 6 to No. 7, Examples No. 4 to No. 5 and No. 10 have a higher degree of freedom in selecting light whose energy is to be absorbed.

[0106] Comparing the examples, Example No. 10 (six-component R2TiO5) shown in FIG. 10 has a greater variety of rare earth trivalent ions having unpaired electrons in the inner 4f orbitals than Example No. 5 (quaternary R2TiO5) shown in FIG. 9, and therefore has a higher degree of freedom in selecting light whose energy is to be absorbed.

[0107] Furthermore, when comparing the average reflectance, average absorptance (average emissivity), and average transmittance of light in the wavelength region (0.5 μm to 2.5 μm), in the case of Example No. 5 shown in FIG. 9, (average reflectance, average absorptance, average transmittance) = (42%, 53%, 5%). In contrast, in the case of Example No. 10 shown in FIG. 10, (average reflectance, average absorptance, average transmittance) = (24%, 74%, 2%). Thus, Example No. 10 has a lower average reflectance, a higher average absorptance, and a lower average transmittance than Example No. 5.

[0108] 9 and 10, Example No. 10 shown in Fig. 10 is less likely to exhibit a "neck" in the absorption band over the entire wavelength range (0.5 μm to 2.5 μm) than Example No. 5 shown in Fig. 9. This makes it possible to ensure a constant absorptance (e.g., 40% or more) over the entire wavelength range (0.5 μm to 2.5 μm).

[0109] In addition, in Example No. 2, similar to Comparative Examples Nos. 6 to 7, a rare earth trivalent ion (Yb 3+ ) is included. Therefore, Example No. 2 has optical properties equivalent to those of Comparative Examples No. 6 to No. 7. Also, Example No. 2 has only one type of Yb 3+ In addition, Y 3+ , La 3+ , Gd 3+ These trivalent rare earth ions do not contribute to the optical properties of Example No. 2 in the wavelength region (0.5 μm to 2.5 μm), but as described above, they contribute greatly to the structural stability, mechanical properties, and thermal properties of Example No. 2. [Explanation of symbols]

[0110] 1: thermal barrier coating system, 2: substrate, 3: bonding layer, 4: thermal barrier layer, 40: segment, 41: gap, L1 to L5: phase boundary

Claims

1. General formula R 2 TiO 5 (R is at least three kinds of rare earth elements), and utilizes excitation energy of at least one kind of the rare earth element to absorb the energy of the light having a specific wavelength included in the infrared wavelength range.

2. The heat-resistant material according to claim 1 , wherein the wavelength of the light is in the range of 0.7 μm to 4 μm.

3. 2. The heat-resistant material according to claim 1, wherein R is at least four of the rare earth elements.

4. The heat-resistant material according to claim 1 , wherein the rare earth titanate has a crystal system of a cubic system.

5. 2. The heat-resistant material according to claim 1, wherein the rare earth titanate contains each of the rare earth elements constituting R in equimolar amounts.

6. A thermal barrier coating system comprising a substrate and a thermal barrier layer having the thermal barrier material of claim 1 disposed on a front side of the substrate.

7. A method for producing the heat-resistant material according to claim 1, comprising the steps of: A manufacturing method comprising: an R determination step of determining R so that the rare earth element having excitation energy corresponding to the energy of the light to be absorbed is included in the light included in the infrared wavelength range.

Citation Information

Patent Citations

  • High-entropy oxides for thermal barrier coating (TBC) top coats

    WO2020142125A2

Cited By

  • High-entropy rare earth titanate ceramic coating material and preparation method thereof

    CN117383926A

  • A high-entropy rare-earth titanate ceramic coating material and its preparation method

    CN117383926B